The interplay between SME owner-managers and the brand-as-a-person. Issue 4 (15th July 2019) - Centeno, Edgar; Cambra-Fierro, Jesus; Vazquez-Carrasco, Rosario; Hart, Susan J.; Dinnie, Keith
Abstract : Purpose: The purpose of this paper is to investigate the largely unexplored conceptualisation of the brand-as-a-person metaphor in small-to-medium-sized enterprises (SMEs) by examining its potential relation with the SME owner-manager, the pathways to its creation and development and the intuitive nature of this relationship. Design/methodology/approach: A grounded theory approach was used, and data were collected through a set of 36 semi-structured interviews with 30 SME owner-managers in various sectors in Mexico. Findings: The results indicate that SME owner-managers intuitively humanise their brands. The study revealed four pathways to develop the brand-as-a-person metaphor in the SME context: through personality traits, tastes and preferences, abilities and knowledge and values, all suggesting that SMEs' brand-as-a-person metaphors are largely an extension of their owner-managers. Research limitations/implications: The paper presents a theoretical framework that illustrates the four pathways to the creation and development of brand-as-a-person that are derived from the brand's relationship with the SME owner-manager. The results of cross-industry semi-structured interviews are limited to a single culture context. Practical implications: SME owner-managers should first undertake an introspective personal assessment of their intuitive and conscious decision-making, as SME owner-managers often make decisions in an intuitive way. The results suggest that they should act in a more conscious, responsible and rational way when formulating their brand strategies. Originality/value: This is the first study to clarify the profound influence of SME owner-managers' personal characteristics, including personality traits, tastes and preferences, abilities and knowledge and values, on the brand-as-a-person metaphor. This study also confirms the intuitive learning strategy formulation of SME owner-managers' branding practices and SMEs' need for a more rational approach to branding.